PLANNING OF MUSHALLA ENGINEERING FACULTY SAMUDRA UNIVERSITY WITH ECO DESIGN CONCEPT - Agus Riki; Meilandy Purwandito; Wan Alamsyah; Nina Fahriana (Program Studi Teknik Sipil, Fakultas Teknik. Universitas Samudra, 2021)
Mushalla is a very important role in the development and teaching of islam, and one of the supporting facilities in the faculty environment as an increase in spiritual activities and to meet the needs of worship. Therefore, with the planning of this mushalla, it is hoped that it can improve the existing infrastructure in the Faculty of Engineering and produce high quality and highly competitive graduates, especially for graduates of the Civil Engineering Study Program at Samudra University. The purpose of planning this mushalla is; designing a mushalla building design with an architectural concept that is comfortable, effective and environmentally friendly or eco design, designing a mushalla building design that is open and blends with nature. Method of collecting data; field survey, location determination, and data processing. Data processing analysis; calculating the area requirements of the room, making alternative plans and visible designs of the mushalla building. The results of this study can be concluded that the land used has an area of 3.100 m². In planning this Mushalla, three design alternatives are planned, namely; The first alternative mushalla design has a total floor area of 2 floors and a floor area of 380 m² with a rectangular design concept, the second alternative mushalla design has 1 floor and a floor area of 228.16 m² with a pentagon design concept, then the third alternative mushalla design has The number of floors is 2 floors and the floor area is 661 m² with the concept of the Space Frame roof design.